Reliability of multigrain indexing for orthorhombic polycrystals above 1 Mbar: application to MgSiO3 post‐perovskite. Issue 1 (10th January 2017) - Langrand, Christopher; Hilairet, Nadège; Nisr, Carole; Roskosz, Mathieu; Ribárik, Gábor; Vaughan, Gavin B. M.; Merkel, Sébastien
Abstract : Experiments and simulations are used to evaluate the applicability of multigrain crystallography for high‐pressure diamond anvil cell experiments. The method allows the retrieval of a large portion of the illuminated sample grains with an average theoretical resolution in grain orientation of 0.02° and a spatial resolution that requires further improvement. Abstract : This paper describes a methodology for characterizing the orientation and position of grains of an orthorhombic polycrystalline material at high pressure in a diamond anvil cell. The applicability and resolution of the method are validated by simulations and tested on an experimental data set collected on MgSiO3 post‐perovskite at 135 GPa. In the simulations, ∼95% of the grains can be indexed successfully with ∼80% of the peaks assigned. The best theoretical average resolutions in grain orientation and position are 0.02° and 1.4 µm, respectively. The indexing of experimental data leads to 159 grains of post‐perovskite with 30% of the diffraction peaks assigned with a 0.2–0.4° resolution in grain orientation. The resolution in grain location is not sufficient for in situ analysis of spatial relationships at high pressure. The grain orientations are well resolved and sufficient for following processes such as plastic deformation or phase transformation. The paper also explores the effect of the indexing parameters and of experimental constraints such as rotation range and step on the validity of the results, setting a basis for optimized experiments.